VARIASI PRODUKSI BIOETANOL DARI LIMBAH KULIT BUAH-BUAHAN MENGGUNAKAN RAGI Saccaromyces Cerevisiae - Nurjanah, Rizki; Aznury, Martha (KINETIKA, 2020)
Bioethanol is ethanol made from plants that contain starch, sugar and other cellulosic plants. The general methods used are hydrolysis and anaerobic fermentation methods. This review aims to compare the results of several studies on the manufacture of bioethanol from various raw materials and the treatment of variations in fermentation pH, type of yeast, and fermentation time. Based on the studies that have been carried out, it can be concluded that the first largest yield of bioethanol is found in a study conducted by Gebregergs et al. (2016) showing that bioethanol yield from banana peels of 45.088% ethanol is obtained at an acid concentration of 1.50% v/v. retention time 21.66 minutes. Then the second largest result was found in research according to Demiray et al. (2018) producing a percent ethanol of 44.9% v/v Â± 55.58 g/L from pomegranate peel raw material. In a study according to Octria et al. (2019), from raw materials of pineapple peel, a percent yield of bioethanol was 30.15% w/w using hydrolysis and anaerobic fermentation methods through the enzyme Saccaromyces cerevisiae.